2015
DOI: 10.1007/s40753-015-0022-x
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Use of Computational Thinking in Linear Algebra

Abstract: In this work, we examine students' ways of thinking when presented with a novel linear algebra problem. Our intent was to explore how students employ and coordinate three modes of thinking, which we call computational, abstract, and geometric, following similar frameworks proposed by Hillel (2000) and Sierpinska (2000). However, the undergraduate honors linear algebra students in our study used the computational mode of thinking in a surprising variety of productive and reflective ways. This paper examines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Furthermore, in the intervention group, students were more likely to move up one or more categories (i.e., performance levels) from the pre-test to the post-test than in their control group. These results are consistent with those reported by Bagley and Rabin (2015), who found that CT could enhance algebra learning. Especially when using various creative and reflective approaches, thus implying that CT involves learning a symbolic representation of language and a wider problem-solving approach.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in the intervention group, students were more likely to move up one or more categories (i.e., performance levels) from the pre-test to the post-test than in their control group. These results are consistent with those reported by Bagley and Rabin (2015), who found that CT could enhance algebra learning. Especially when using various creative and reflective approaches, thus implying that CT involves learning a symbolic representation of language and a wider problem-solving approach.…”
Section: Discussionsupporting
confidence: 93%
“…This broader approach to understanding CT is supported by Bagley and Rabin (2015), who showed that CT could enhance algebra learning. Their study revealed that undergraduate students use computational modes of thinking in various creative and reflective ways when working with linear algebra, thus indicating that CT involves learning a symbolic representation of language and a broader problem-solving process.…”
Section: Algebraic Thinking In Relation To Computational Thinkingmentioning
confidence: 87%
“…De posse disto, é muito comum a abordagem do PC no ensino de engenharia nas disciplinas de Lógica de Programac ¸ão de Computadores [Valencia et al 2022], e nas disciplinas de Introduc ¸ão à Sistemas Robóticos [Wu et al 2019], no ensino de álgebra [Bagley and Rabin 2016], no ensino de inteligência artificial [Silapachote and Srisuphab 2017], sistemas complexos [Berland and Wilensky 2015], matemática discreta [Liu and Wang 2010].…”
Section: Trabalhos Relacionadosunclassified
“…Regarding the latter claim, some studies pointed out the importance of balancing the use of geometry in order to avoid students' view to be limited to geometric vectors: e.g., (Gueudet-Chartier, 2004), (Harel, 2017). In addition, there is another report (Bagley & Rabin, 2016) providing evidence for the utility of computational reasoning and questioning the view that computational thinking is mathematically unsophisticated among three modes of thinking: abstract, geometric, and computational. These remarks indicate that the use of geometry in teaching linear algebra and its effectiveness should be additionally investigated.…”
Section: Introductionmentioning
confidence: 99%